Novel Non-paralytic Shellfish Toxin and Non-spirolide Toxicity to Finfish, Brine Shrimp, and Rotifer Observed in a Culture of the Dinoflagellate Alexandrium insuetum Isolated From the Coastal Water of China - Song, Xiaoying; Zhai, Xinyu; Hao, Shuang; Shang, Lixia; Deng, Yunyan; Chai, Zhaoyang; Chen, Junhui; Hu, Zhangxi; Tang, Ying Zhong (Frontiers in Marine Science, 2021)
The genus Alexandrium is one of the major harmful algal blooms (HABs)-forming dinoflagellate group and at least half of ~40 described species have been reported to produce paralytic shellfish toxins (PSTs). The potentially harmful species Alexandrium insuetum has been reported from many countries of Asia and Europe, and to have PSP toxicity, but no mortality of marine animals was observed during its bloom. Therefore, it is ecologically important to characterize the possible toxicity and toxins of this organism. Here, based on the establishment of two clonal cultures through cyst germination collected from the Yellow Sea, we identified Alexandrium insuetum from China as the first record via LM and SEM observations and phylogenetic analyses. The cultures of A. insuetum were further observed to be toxic to finfish and zooplankton and deleterious to rotifer eggs via laboratory bioassays. The exposure bioassays using rotifer (Brachionus plicatilis), brine shrimp (Artemia salina), and larval finfish (Oryzias melastigma) demonstrated that A. insuetum caused significant lethal effects on finfish and zooplankton species. Rotifer bioassays using cell-free culture medium, heat-treated cultures, and water, methanol and trichloromethane extracts of algal cells revealed that A. insuetum produced heat-labile, water-soluble toxin(s) that could be excreted from A. insuetum cells and steadily accumulated in the medium during the growth phases. Hatching success of rotifer eggs was also found to be seriously affected by the exposure to A. insuetum. Importantly, UPLC (or LC)-MS-MS analyses suggest the above-described toxicity of A. insuetum was caused by neither PSTs nor spiroimines (13-desmethyl spirolide C and gymnodimine). Collectively, our findings demonstrated the novel toxicity to finfish and zooplankton in A. insuetum is ecologically important in not only possibly contributing to population dynamics and even the formation of HABs of the species, but also affecting the on-the-spot survival and the reproduction potency of marine animals. The present work is believed to set a cornerstone for the monitoring and risk assessment of the species along the coastal waters of China and for understanding the general ecology of A. insuetum.